(untitled) (Swiss Medical Weekly, 2020)
BACKGROUND Renal replacement therapy for paediatric end-stage renal disease (ESRD) has developed steadily since its introduction five decades ago. Continuous and long-term analysis of patient outcomes is essential for quality control. METHODS The Swiss Paediatric Renal Registry, founded in 1970, includes patients diagnosed with ESRD, defined as dialysis for more than three months or renal transplantation, at age <20 years. Here we describe the incidence, primary renal disease, treatment modalities and long-term outcomes over 45 years. RESULTS This paper reports on 367 children and adolescents treated with chronic renal replacement therapy in Switzerland. Incidence was 5.4 per million children per year, with a tendency to increase over time. The primary renal disease was congenital anomalies of the kidney and the urinary tract in 133 (36%), monogenetic hereditary diseases in 122 (33%) and acquired diseases in 112 (31%) patients. The first renal replacement therapy was haemodialysis in 194 (53%), peritoneal dialysis in 116 (32%) and pre-emptive renal transplantation in 57 (15%) patients. Over the years, pre-emptive renal transplantation became more frequent (34% of all first renal replacement therapies in 2006–2015), reducing the duration of dialysis. Median time on dialysis until transplantation decreased from 1.60 years in 1981–90 to 0.34 years in 2010–15. Over the four decades 1970–80, 1981–90,1991–2000 and 2001–10, the one-year graft survival rate improved from 0.76 to 0.80, 0.89 and then 0.96; and the five-year graft survival rate improved from 0.44 to 0.64, 0.84 and 0.89, respectively. The five-year patient survival rates for the four decades were 0.83, 0.99, 0.93 and 0.94; and the 10-year patient survival rates were 0.75, 0.96, 0.88 and 0.94, respectively. In the four cohorts starting renal replacement therapy in the 70s, 80s, 90s and 00s, the number of children alive after five years of renal replacement therapy increased from 15 to 24, 47 and then 45 respectively. In total, 29 patients (8%) died during chronic renal replacement therapy with ESRD before the age of 20 years. CONCLUSION Over time, a higher number of children on renal replacement therapy survived, graft survival improved, and the duration of dialysis before renal transplantation decreased.